2014
DOI: 10.1185/03007995.2014.912983
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of luseogliflozin as monotherapy in Japanese patients with type 2 diabetes mellitus: a randomized, double-blind, placebo-controlled, phase 3 study

Abstract: Objective: Luseogliflozin -a novel, orally bioavailable, 1-thio-D-glucitol derivative and a selective sodium glucose cotransporter 2 inhibitor -has shown efficacy and tolerability in previous phase 2 studies. This phase 3, randomized, double-blind, placebo-controlled, comparative study aimed to confirm the superiority of 24 week luseogliflozin 2.5 mg monotherapy over placebo in reducing hemoglobin A1c (HbA1c) levels in Japanese patients with type 2 diabetes mellitus (T2DM). Methods:Patients with HbA1c levels o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
123
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 123 publications
(136 citation statements)
references
References 19 publications
12
123
1
Order By: Relevance
“…*P< 0.001 (compared to baseline using the one-sample t-test). CI, confidence interval; FPG, fasting plasma glucose; HbA1c, hemoglobin A1c; SD, standard deviation ies [6,7,11]. It was also comparable to that observed in a 52-week study of sitagliptin (1.7%), a DPP-4 inhibitor known for its low incidence of hypoglycemia when administered as monotherapy [12].…”
Section: (Compared With Baseline By One-sample T-test)supporting
confidence: 70%
See 3 more Smart Citations
“…*P< 0.001 (compared to baseline using the one-sample t-test). CI, confidence interval; FPG, fasting plasma glucose; HbA1c, hemoglobin A1c; SD, standard deviation ies [6,7,11]. It was also comparable to that observed in a 52-week study of sitagliptin (1.7%), a DPP-4 inhibitor known for its low incidence of hypoglycemia when administered as monotherapy [12].…”
Section: (Compared With Baseline By One-sample T-test)supporting
confidence: 70%
“…Our previous study showed that luseogliflozin significantly reduced body weight at Week 24 [7]. Since the present study revealed that the weight reduction could be maintained for longer than 24 weeks, luseogliflozin may be more beneficial for the long-term management of patients with type 2 diabetes mellitus where weight gain is undesirable.…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…These studies are registered at the Japan Pharmaceutical Information Center (identifier: JapicCTI‐090908, JapicCTI‐101191 and JapicCTI‐111661)2, 3, 4. The major inclusion criteria were as follows: Japanese patients with type 2 diabetes mellitus receiving diet and exercise therapy alone, age ≥20 years and with glycated hemoglobin levels ≥6.9% to ≤10.5%.…”
mentioning
confidence: 99%